Resistance Monitoring of Nilaparvata lugens to Pymetrozine Based on Reproductive Behavior - Xin-Yu Song; Yu-Xuan Peng; Yang Gao; Yan-Chao Zhang; Wen-Nan Ye; Pin-Xuan Lin; Cong-Fen Gao; Shun-Fan Wu (Insects, 2023)
On the basis of the inhibition effects of pymetrozine on the reproductive behavior of N. lugens, we established a bioassay method to accurately evaluate the toxicity of pymetrozine in N. lugens and clarified the level of pymetrozine resistance of N. lugens in the field. In this study, pymetrozine’s effects on the fecundity of N. lugens were evaluated using the topical application method and rice-seedling-dipping method. Moreover, the resistance of N. lugens to pymetrozine in a pymetrozine-resistant strain (Pym-R) and two field populations (YZ21 and QS21) was determined using the rice-seedling-dipping method and fecundity assay methods. The results showed that treatment of N. lugens third-instar nymphs with LC15, LC50, and LC85 doses of pymetrozine resulted in a significantly reduced fecundity of N. lugens. In addition, N. lugens adults treated with pymetrozine, using the rice-seedling-dipping and topical application method, also exhibited a significantly inhibited fecundity. Using the rice-stem-dipping method, pymetrozine resistance levels were shown to be high in Pym-R (194.6-fold), YZ21 (205.9-fold), and QS21 (212.8-fold), with LC50 values of 522.520 mg/L (Pym-R), 552.962 mg/L (YZ21), and 571.315 (QS21) mg/L. However, when using the rice-seedling-dipping or topical application fecundity assay method, Pym-R (EC50: 14.370 mg/L, RR = 12.4-fold; ED50: 0.560 ng/adult, RR = 10.8-fold), YZ21 (EC50: 12.890 mg/L, RR = 11.2-fold; ED50: 0.280 ng/adult; RR = 5.4-fold), and QS21 (EC50: 13.700 mg/L, RR = 11.9-fold) exhibited moderate or low levels of resistance to pymetrozine. Our studies show that pymetrozine can significantly inhibit the fecundity of N. lugens. The fecundity assay results showed that N. lugens only developed low to moderate levels of resistance to pymetrozine, indicating that pymetrozine can still achieve effective control on the next generation of N. lugens populations.